ANALISIS KESALAHAN PENULISAN PARAGRAF DALAM SKRIPSI MAHASISWA IAIN BUKITTINGGI - Jasmienti Jasmienti (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2018)
The problem of the research was various unrevealed errors found in students’ theses at Informatics and Computer Engineering Education Department of IAIN Bukittinggi. This study is aiming at describing the errors found in the students’ theses. This is a qualitative research which describes the errors of students’ writing theses. The data were collected through the technique bof documentary study. The source of data was the students’ theses. The research consisted of five phases; Reading, Identifying, Coding, Summarizing, Displaying, and Summarizing the data. The result describes five errors in students’ theses namely: uncohesive, uncoherent, incomplete, undeveloped, and unsequential arrangement of paragraphs.